2015
DOI: 10.5194/amt-8-1407-2015
|View full text |Cite
|
Sign up to set email alerts
|

Infrared and millimetre-wave scintillometry in the suburban environment – Part 2: Large-area sensible and latent heat fluxes

Abstract: Abstract.A millimetre-wave scintillometer was paired with an infrared scintillometer, enabling estimation of large-area evapotranspiration across northern Swindon, a suburban area in the UK. Both sensible and latent heat fluxes can be obtained using this "two-wavelength" technique, as it is able to provide both temperature and humidity structure parameters, offering a major advantage over conventional singlewavelength scintillometry. The first paper of this two-part series presented the measurement theory and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…Compared with the magnitude of ET observed in other landscapes (grasslands, farmlands, and forests), these values were not small (Yan and Qiu, 2016). The daily ET in our study could reach to 6 mm day −1 , much higher than 1-3 mm day −1 observed in other urban areas located in temperate zones ( [4,29,30]). Urban ET is very obvious and cannot be neglected for water and environmental management.…”
Section: Relationship Between Urban Et and Precipitation (P)mentioning
confidence: 78%
“…Compared with the magnitude of ET observed in other landscapes (grasslands, farmlands, and forests), these values were not small (Yan and Qiu, 2016). The daily ET in our study could reach to 6 mm day −1 , much higher than 1-3 mm day −1 observed in other urban areas located in temperate zones ( [4,29,30]). Urban ET is very obvious and cannot be neglected for water and environmental management.…”
Section: Relationship Between Urban Et and Precipitation (P)mentioning
confidence: 78%
“…Basel (Christen and Vogt 2004), Swindon (Ward et al 2014), London (Crawford et al 2017). As highlighted by Ward et al (2015b), there is still a need for long-term scintillometer measurements of sensible and latent heat fluxes in urban areas that capture both the seasonal and inter-annual variability. Therefore, such long-term measurement campaigns could help determine to what extent the observed variability of heat fluxes is caused by different surface characteristics or by weather conditions.…”
Section: Discussionmentioning
confidence: 99%
“…One approach for achieving this would be to work with structure parameters directly, rather than fluxes (e.g. Wood et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Each C 2 n measurement is made up of a combination of the three unknowns: C 2 T , C 2 q and C T q . As C 2 n from large aperture optical or near-infrared scintillometers is almost entirely made up of temperature fluctuations (C 2 T ), the (usually small) contributions from C T q and C 2 q can be approximated using the Bowen ratio, β (Wesely, 1976;Moene, 2003):…”
Section: Obtaining Structure Parameters From Scintillometrymentioning
confidence: 99%
See 1 more Smart Citation